2019
DOI: 10.1530/edm-19-0040
|View full text |Cite
|
Sign up to set email alerts
|

Clinical presentation and management of primary ovarian neuroendocrine tumor in multiple endocrine neoplasia type 1

Abstract: Summary Multiple endocrine neoplasia type 1 (MEN1) is an autosomal dominant condition characterized by parathyroid, anterior pituitary and enteropancreatic endocrine cell tumors. Neuroendocrine tumors occur in approximately in 5–15% of MEN1 patients. Very few cases of ovarian NETs have been reported in association with clinical MEN1 and without genetic testing confirmation. Thirty-three-year-old woman with MEN1 was found to have right adnexal mass on computed tomography (CT). Attempt at laparoscopic removal wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Multiple endocrine neoplasia Type I (MEN I) is an autosomal dominant inherited syndrome, which is associated with parathyroid, anterior pituitary and enteropancreatic endocrine cell tumors. 111 , 112 The MEN I gene is a tumor suppressor gene, which is located on chromosome 11q13. The MEN I gene encodes the protein menin.…”
Section: Hereditary Gynecologic Cancer Syndromesmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple endocrine neoplasia Type I (MEN I) is an autosomal dominant inherited syndrome, which is associated with parathyroid, anterior pituitary and enteropancreatic endocrine cell tumors. 111 , 112 The MEN I gene is a tumor suppressor gene, which is located on chromosome 11q13. The MEN I gene encodes the protein menin.…”
Section: Hereditary Gynecologic Cancer Syndromesmentioning
confidence: 99%
“… 113 MEN II is an autosomal dominant inherited syndrome characterized by medullary thyroid carcinoma, with or without pheochromocytoma and hyperparathyroidism. 111 , 112 MEN II is divided into three subtypes: MEN IIA (Sipple’s syndrome), MEN IIB and familial medullary thyroid carcinoma. MEN II is caused by the rearranged during transfection (RET) gene mutations.…”
Section: Hereditary Gynecologic Cancer Syndromesmentioning
confidence: 99%
“…Other tumor types are associated with MEN1, including adrenal cortex tumors, foregut carcinoids, thyroid tumors, and meningiomas. In recent years, ovarian and uterine tumors related to MEN1 have also been reported (18)(19)(20). Studies have found that women with MEN1 have a significantly higher risk of breast cancer (21).…”
Section: Men1mentioning
confidence: 99%
“…Ovarian NETs are rare and comprise 0.1% of all ovarian tumors. To date, few cases of primary ovarian NETs in women with MEN1 syndrome have been described in association with clinical manifestations of MEN1, but without genetic testing (106)(107)(108)(109) NET in a 33-year-old woman (109). Also, the case of an atypical ovarian carcinoid has been described as the first manifestation of an otherwise occult MEN1 syndrome in a 30-year old woman, who later developed a contralateral lesion two years after initial diagnosis (108).…”
Section: Other Neoplasmsmentioning
confidence: 99%